Integrated Design and Experiment of a Micro-Vibration Isolation and Pointing Platform for Large Space Optical Payloads Based on Voice Coil Motors - Yilin Guo; Jian Zhou; Zehao Gao; Bo Feng; Minglong Xu (Sensors)
This paper presents the design of an integrated micro-vibration isolation and pointing platform with a four-leg structure, incorporating pitch and yaw adjustment functions using voice coil motors. The primary objective is to mitigate the impact of spacecraft-generated micro-vibrations on the pointing accuracy and imaging clarity of large space optical payloads while adhering to lightweight requirements. The research methodology encompasses three main phases. Initially, a simplified dynamic model of the integrated platform is established, and dynamic control equations are derived based on the proportional–integral–derivative (PID) control strategy. The effects of centroid deviation and control parameters on the control efficacy are analyzed. Subsequently, a principle prototype of the two-dimensional micro-vibration isolation and pointing platform is designed, detailing the development of the membrane, actuator, legs, and integrated system. Finally, a ground test verification system is implemented under gravity unloading conditions using elastic strings. The experimental results demonstrate the platform’s effective vibration isolation and pointing capabilities, achieving a 23 dB attenuation effect at the fundamental frequency. Furthermore, the PID control algorithm exhibits enhanced isolation performance at low frequencies and facilitates directional tracking of target signals.